Tinjauan Naratif tentang Keterkaitan Religiusitas, Self-Regulation,Emotional Eating, dan Status Gizi Lebih - Nasir, Narila Mutia; Rarez, Moga Talitha (Journal of Religion and Public Health, 2026)
Background: Overweight and obesity remain major global public health challenges. Beyond energy imbalance, nutritional status is also influenced by psychological factors, particularly emotional eating and self-regulation. Religiosity has been recognized as a psychological resource that may strengthen emotion regulation and self- egulation; however, the mechanisms linking religiosity, self-regulation, emotional eating, and nutritional status have not been comprehensively synthesized. Objective: To synthesize scientific evidence on the relationships among religiosity, self-regulation, emotional eating, and nutritional status and to explain the conceptual mechanisms underlying these associations. Methods: A narrative literature review with narrative synthesis was conducted. Literature was searched in Google Scholar, PubMed, ScienceDirect, and SpringerLink. Of 186 identified articles, 17 met the inclusion criteria and were included in the final synthesis. Results: Emotional eating increases the risk of overweight and obesity by promoting the consumption of energy-dense foods in response to emotional distress. This process involves activation of the hypothalamic–pituitary–adrenal axis, elevated cortisol levels, stimulation of the reward pathway, and impaired appetite regulation. Self-regulation reduces the adverse effects of emotional eating by improving control over eating impulses. Religiosity further strengthens emotion regulation and self-regulation through the internalization of religious values and practices, thereby reducing the tendency toward emotional eating. Conclusion: This review proposes a conceptual model in which religiosity indirectly influences nutritional status by enhancing emotion regulation, self-regulation, and control of emotional eating. These findings contribute to a biopsychosocial-spiritual approach to health promotion and obesity prevention. Keywords: emotional eating; narrative literature review; nutritional status; religiosity; self-regulation